Exact Weighted-FBP Algorithm for Three-Orthogonal-Circular Scanning Reconstruction - Hongli Hu; Jianzhou Zhang (Sensors, 2009)
Recently, 3D image fusion reconstruction using a FDK algorithm along threeorthogonal circular isocentric orbits has been proposed. On the other hand, we know that 3D image reconstruction based on three-orthogonal circular isocentric orbits is sufficient in the sense of Tuy data sufficiency condition. Therefore the datum obtained from three-orthogonal circular isocentric orbits can derive an exact reconstruction algorithm. In this paper, an exact weighted-FBP algorithm with three-orthogonal circular isocentric orbits is derived by means of Katsevich’s equations of filtering lines based on a circle trajectory and a modified weighted form of Tuy’s reconstruction scheme.